Structuring the Mediation Effect of Organizational Commitment between Abusive Supervision and Employees Work Performance - Kombate, Bienmali; Adamseged, Hanna Yeshinegus (International Journal of Contemporary Economics and Administrative Sciences, 2023)
The topic of abusive supervision in the workplace is among the most studied subjects in different disciplines, including psychology, organizational behavior, and related fields. However, researchers and scholars ignore the mediation effect of organizational commitment in the relationship between abusive supervision and employee work performance. Moreover, there is a lack of studies undertaken on this issue in the public sector. This research data was collected in the Republic of Togo central government institutions and state-owned organizations, which are of particular importance and are filled with civil servants. The random sampling method was applied to collect the data from 214 respondents through structured survey questionnaires. The finding revealed that organizational commitment is mitigating the negative effect of abusive supervision on employees' performance. The results also showed that even though employees with normative commitment are most attached to the organization, they are less productive than individuals with affective and normative commitment. Finally, the study concluded that civil servant with a strong organizational commitment doesn't show up on their supervisor's behavior but instead bear the character of "good citizenship."